Recovery Potential Study of Waste Containing Carbohydrate Starch as an Alternative Raw Material of Bioethanol in Hospital - Prasetiyo, Bagus Dadang; Sholihah, Qomariyatus (Indonesian Green Technology Journal, 2024)
The aim of this research is to identify waste to assess the potential recovery of hospitalized rice waste as alternative raw material source of bioethanol. Values are calculated based on the alcoholic fermentation and distillation process which was measured by using Alcohol Meters and Cost Benefit Analysis (CBA) computation. The methodological steps used are starting with a study idea which includes literature study, waste flow system containing carbohydrate starch and determining the distribution of characteristics of waste containing carbohydrate starch. The results of the study ideas were then followed up with an initial evaluation of the potential through interviews and questionnaires. After the initial evaluation data has been collected, further data processing will be carried out using a structured survey of rice waste to the sources of production and the management of existing rice waste is evaluated. Thus, data on generation, characteristics and composition of rice waste were obtained through sampling. Data analysis was performed using statistical tests and laboratory tests, as well as the calculation of CBA. The average arise of hospitalized rice waste is 69.34 kg/day, and the average results of ethanol through the fermentation and distillation process of hospitalized rice waste is 80%. Using IRR and NPV  in CBA calculations at each of profits/benefits. Rice waste has the potential recovery as an alternative source of raw material for bioethanol, and has a value profits and benefits greater than value of the cost. IRR of rice waste from Hospital “X” is 21.54%